Antibiotic use, knowledge, and practices of milk vendors in India's informal dairy value chain - Sharma, Garima; Leahy, Eithne; Deka, Ram Pratim; Shome, B.R.; Bandyopadhyay, S.; Dey, Tushar K.; Goyal, N.K.; Lundkvist, Å.; Grace, Delia; Lindahl, Johanna F. (Frontiers Media, 2022)
Background: Milk vendors play an important role in India's dairy value chain; however, their food safety practices are poorly understood. From a milk safety perspective, vendor behavior is significant because it has the potential to affect both consumer and producer behavior. This study describes the types of milk vendors in two Indian states, in an attempt to investigate vendors' hygienic knowledge and practices toward safety and antimicrobial resistance (AMR).